Nexus between Financial Literacy and Financial Behavior: Theoretical and Empirical Insights (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2024)
Financial literacy empowers individuals to make informed financial behaviors, leading to better planning and management of life milestones like education, housing, savings, and retirement. This study analyzed the nexus between financial literacy and financial behavior among individuals by synthesizing existing theoretical frameworks and empirical research. The analysis reveals that financial literacy is significantly impacted by a combination of demographic (gender, income), educational (level), and personality characteristics (financial behavior, attitude, and influence). These findings highlight the multifaceted nature of financial literacy and financial behavior and underscore the need for targeted interventions that address the diverse factors shaping students' financial knowledge and decision-making abilities.